Jim’s Pursuit of Happiness in Dr. James R. Doty’s in Into The Magic Shop - Aliyah Dewi Kinanti; Danu Wahyono (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2026)
This study aims to analyze Jim’s pursuit of happiness in Into the Magic Shop. The study focuses on how Jim seeks happiness through emotional healing, personal growth, and self-awareness after experiencing a painful childhood filled with poor conditions, family conflict, emotional neglect, and insecurity. These difficult experiences shape Jim’s personality and motivate him to seek happiness, emotional fulfillment, and inner peace. A psychological approach based on Maslow’s Hierarchy of Needs is used in this study to examine how Jim fulfills his physiological needs, safety needs, love and belonging needs, and esteem needs throughout his life journey. This study employs a qualitative-descriptive method by analyzing dialogues, narrative descriptions, and significant events in the novel through close reading. The discussion shows that Jim's motivation to seek happiness comes from his difficult childhood experiences. Growing up in a poor family, facing emotional neglect, family conflict, and insecurity, many of his basic needs went unmet. These conditions drive him to search for safety, acceptance, self-worth, and a better future. The analysis also reveals that Jim pursues happiness through several stages of personal growth. His emotional change starts when he meets Ruth, who teaches him meditation, breathing techniques, and emotional self-control. These practices help him find inner peace and emotional stability. Furthermore, Jim grows personally by learning self-compassion, empathy, and positive ways to respond to life’s challenges. His self-awareness grows as he recognizes his potential, pursues his dream of becoming a doctor, and reflects on the meaning of success. The findings indicate that Jim finally realizes that happiness is not achieved through wealth, status, or material success alone, but through inner peace, meaningful relationships, empathy, generosity, and contributing to the well-being of others.